Strategi Pengembangan Ekonomi Lokal Desa Wisata Kampung Patin Kabupaten Kampar (Menurut Ekonomi Syariah) - Melina, Ficha; Rudini, Irwan; Mahyarni, Mahyarni; Yanti, Yanti (UIR Press, 2022)
Local Economic Development which has the potential to become a tourist village in District XIII Koto Kampar is Koto Mesjid Village and this is a process where local governments and community organizations are involved to encourage business activities to create jobs. The aim of the research is to know. the strategy. development. local economy and the impact of the Kampung Patin Tourism Village according to Islamic economics. This research includes descriptive explanatory research, and descriptive qualitative methods. The results of the research, the local economic development strategy through the tourist village of Kampung Patin, namely: a. Carry out counseling, training and community development in the field of tourism and culture. b. Increase community participation by optimizing community partnerships in the development and management of tourism objects. c. Increase promotion in the field of culture and tourism. d. Increasing partnerships between the Government and the community, including the business world or BUMD in an effort to develop facilities and infrastructure for superior tourist objects. The impact of the local economic development strategy through the Kampung Patin tourism village shows a positive impact, for the economic, socio-cultural and environmental development of the Village itself, government revenues through tourist retribution.